Adherencia al tratamiento antimalárico en comunidades rurales del distrito de Iquitos, Loreto 2024 - Parano Soria, Katherine Jeanynne (2025)
Objective: To determine the factors related to adherence to antimalarial treatment in rural communities of the Iquitos district, Loreto, 2024. Methods: This was an observational, descriptive, cross-sectional study with a correlational design. A total of 107 individuals diagnosed with malaria were selected from four rural communities in the Iquitos district: Santa Rita de Nanay, Fray Martín de Porres, San José de Lupuna, and Manacamiri. Data confidentiality and privacy were preserved through coding and the application of informed consent. Data analysis was conducted using SPSS Statistics version 26,0. Results: Most patients showed medium adherence to antimalarial treatment (41,1%), followed by low adherence (30,8%) and high adherence (28%). Using the Chi-square test, statistically significant relationships were found between treatment adherence and clinical factors such as the presence of chills (p=0,003), muscle pain (p=0,034), and pallor (p=0,026). Epidemiological factors significantly associated with adherence included a family history of malaria (p=0,013) and access to the health center (p=0,017). Conclusions: There is a statistically significant relationship between adherence to antimalarial treatment and the presence of chills, muscle pain, pallor, family history of malaria, and access to the health center.